Putting the 'Research' into Research Librarian. Issue 2 (3rd April 2018) - Duffield, Nel; Attar, Helen; Royals, Jaime
Abstract: Librarians in academic libraries are required to support the activities of researchers during the entire scholarly communication life cycle. Although we have a deep understanding of all the stages of the process, we have not often directly experienced it for ourselves. The authors of this paper sought out the opportunity to participate in a research project in order to give them a new perspective on the research process and deepen their credibility with the academics they support. Lessons learned during this process may help other librarians decide if they would like to pursue similar opportunities.